Enhancing Organizational Development through Principal Leadership to Improve Teacher and Staff Work Discipline - Pisriwati, Siti Atwano; Hardi, Yuwono; Siswanto, Deny Hadi (Journal of Organizational and Human Resource Development Strategies, 2024)
This research aims to detail and explain the role played by the principal in improving the work discipline of teachers and employees at particular private high school in Yogyakarta, Indonesia. The method used in this study is descriptive qualitative research using purposive sampling techniques. In this context, school principals are faced with five main tasks that must be completed in order to improve the work discipline of teachers and employees at the school. Apart from that, there are also two problems faced by school principals in trying to achieve this goal. The research results show that the principal at the school has the responsibility to plan and communicate effectively, direct collaboration between staff, design learning programs, manage school facilities and finances, and create a supportive school environment. One of the obstacles faced is the lack of discipline shown by teachers and employees in completing their tasks. This shows the need for appropriate action from the school principal to overcome this problem in order to improve performance and discipline in the school environment.